(untitled) (Research, Society and Development, 2021)
Introduction: Autoimmune diseases refer to a spectrum of conditions in which the immune system mistakenly attacks the body itself, an autoimmune response that often involves unregulated adaptive immunity (mediated by B and T lymphocytes) to anatomical autoantigens such as insulin. Objective: To demonstrate a case report of Sjögren’s Syndrome diagnosed after SARS-CoV-2 infection in a patient with latent adult autoimmune diabetes (LAD), in order to hypothesize the relationship between the virus and the development of the disease. Methodology: this article is a clinical case study with a qualitative and descriptive perspective, which consists of a research in which, in general, it takes place with direct data collection, in which the researcher is the indispensable instrument. Case report: After infection with SARS-CoV-2 in February 2020, the patient, after presenting tearing eyes, joint pain, xerophthalmia, xerostomia and skin rash, detailed physical examination data was collected, and additional tests were requested – hematological (blood count, amylase, serum calcium, alkaline phosphatase) and imaging (ultrasound of the parotid glands) – for making the diagnosis, which revealed changes in serum amylase levels (300 U/l), distributed by the parotid parenchyma bilaterally , with an aspect suggestive of an inflammatory process and diagnosed with Sjögren’s Syndrome. Final considerations: It is believed that Covid-19 has clinical characteristics similar to autoimmune diseases, as both share major immune reactions of the pathogenesis, and that Sars-CoV-2 can alter self-tolerance and generate autoimmune responses through cross-reactivity with cells host, as explained by the case, in relation to Sjögren’s Syndrome.